Pojok Baca Berbasis Literasi Budaya sebagai Upaya Peningkatan Intelektual dan Karakter Generasi Muda di Desa Mira Kabupaten Pulau Morotai - Tonra, Wilda Syam; Christi Kasiuhe, Jeane; Tohau, Ahmad; Ikhsan, Muhammad (Faculty of Cultural Studies, Universitas Brawijaya, 2023)
Mira Village is one of the villages in Morotai Islands Regency that is rich in culture. To reach Mira Village, one must depart from the university by motorboat for 12 hours to Morotai Island, followed by a 2-hour ride by passenger car. The distance from the university to Mira Village is approximately 235 km. Mira Village also has a tourist attraction worth visiting, namely a waterfall located in a resident's garden, with a distance of approximately 1 km from the village to the waterfall. However, despite this potential, Mira Village still lags behind in the education sector. One of the issues is the inadequate internet access, which causes children to fall behind in their learning. If this situation continues unaddressed, the children's literacy skills will decline. To minimize these problems, at least one corner/library is needed for children to study. Another problem is that some teenagers in Mira village choose to marry young, which reduces their desire to continue their education to a higher level. Therefore, there needs to be a program that can combine education, character, and culture in one place. This program is called PPK Ormawa, with its main activity being the development of a reading corner. The reading corner is equipped with science books and fairy tales, as well as other activities such as storytelling, reading and writing instruction, and cultural literacy. The PPK Ormawa program with its reading corner initiative was implemented in July-August 2022 by nine students from the Mathematics Education Program at Khairun University. Introducing culture and literacy to children at an early age is crucial for enhancing the intellectual and character development of the young generation in Mira Village. Keywords: Reading corner; cultural literacy; young generation; intellectual and character of the young generation